Comparison of 5km running performance after 24 and 72 hours of passive recovery - Bosak, A.; Bishop, P.; Green, M.; Hawver, G.; Iosia, M. (The Sport Journal, 2009)
Abstract Recovery from a hard running effort determines when a runner can run at an intense level again. Overtraining is often caused by insufficient recovery, which ultimately hurts endurance performance. The number of recovery hours needed to sufficiently restore the body back to peak racing condition is unknown. The purpose of this study was to compare 5km running performance after 24 hours and 72 hours of recovery. Twelve well-trained runners (9 males and 3 females) completed two successive 5km performance trials on two separate occasions. Immediately following the baseline 5km trial, runners recovered passively for 24 hrs (R24) and 72 hrs of passive recovery (R72), and then performed a second 5km trial. The 5km time trial sessions were separated by 6-7 days of normal training and performed in a counterbalanced order. R24 (19:59 + 1.9 min) was significantly (p = 0.03) slower than baseline (19:49 + 1.9 min). However, no significant differences (p = 0.21) were found between R72 (19:30 + 1.5 min) and baseline (19:34 + 1.6 min). HRave for R24 (177.3 + 6.3 b/min) was the same as baseline (177.3 + 7.3 b/min), yet R72 HRave (177.9 + 6.3 b/min) was significantly higher (p = 0.04) than baseline (175.4 + 6.5 b/min). RPEend for R24 (19.5 + 0.8) was not significantly different (p = 0.39) than baseline (19.6 + 0.8), but R72 RPEend (19.8 + 0.6) was significantly (p = 0.01) greater than baseline (19.3 + 0.9). For the R24 trials, 9 participants ran a mean 17.4 + 12.1 secs slower and 3 participants ran a mean of 13.3 + 6.8 secs faster than baseline. During R72, three individuals ran a mean 10.3 + 5.7 secs slower, five individuals ran a mean 17.4 + 12.9 secs faster, and four individuals ran within 3.3 + 1.8 secs of their first run. Results indicate that 72 hrs of passive recovery, on average, permits maintenance of successive 5km time trial performance, yet individual variability existed regarding rate of decline of 2nd trial performance. Future research is needed to determine if a longer or shorter recovery time will maintain or improve 5km racing performance.